TLE uncertainty estimation using robust weighted differencing. Issue 10 (15th May 2017) - Geul, Jacco; Mooij, Erwin; Noomen, Ron
Highlights: Robust weighted differencing (WD) is used to estimate TLE covariance only requiring public TLE data. WD estimates TLE error characteristics more accurately than pairwise differencing. WD is validated using GPS for a very low-Earth orbit of GOCE for classic and enhanced TLEs. Abstract: Accurate knowledge of satellite orbit errors is essential for many types of analyses. Unfortunately, for two-line elements (TLEs) this is not available. This paper presents a weighted differencing method using robust least-squares regression for estimating many important error characteristics. The method is applied to both classic and enhanced TLEs, compared to previous implementations, and validated using Global Positioning System (GPS) solutions for the GOCE satellite in Low-Earth Orbit (LEO), prior to its re-entry. The method is found to be more accurate than previous TLE differencing efforts in estimating initial uncertainty, as well as error growth. The method also proves more reliable and requires no data filtering (such as outlier removal). Sensitivity analysis shows a strong relationship between argument of latitude and covariance (standard deviations and correlations), which the method is able to approximate. Overall, the method proves accurate, computationally fast, and robust, and is applicable to any object in the satellite catalogue (SATCAT).